ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Septi Wulandari Santoso, 15.05.52.0351; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
This study aims to test and analyze the factors that influence profitability in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. Independent variables consist of Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Company Size (UP) while the dependent variable is Profitability (ROE). This study uses secondary data. The sampling method is purposive sampling. The analysis used is descriptive statistics, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression analysis, test coefficient of determination, F test, t test using SPSS 23 for Windows. 2 The results showed that the Current Ratio had a significant positive effect on Profitability, Total Asset Turnover had a significant positive effect on Profitability, Company Size had a significant positive effect on Profitability, while Debt to Equity Ratio had a positive and insignificant effect on Profitability.